FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR - Cornellista, Maria Ancella; Sudirgo, Tony (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The objective of this study is to examine and obtain empirical evidence of the effect of profitability, growth opportunity, and leverage on cash holding in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. This study used secondary data in the form of company financial statements. The sample selection in this study used purposive sampling method based on certain criteria which were processed using the Eviews 12.0 program. The amount of data obtained is 273 data for 3 years. The results of this study indicate that profitability has a significant positive effect on cash holding, growth opportunity have no effect on cash holding, while leverage has a significant negative effect on cash holding.